Repair process for ceramic glaze defects

Through the optimized ceramic glaze defect repair process, the repair base material and repair glaze of specific formulas are used, combined with shuttle chamber kiln calcining technology, the problems of low repair layer strength, large firing shrinkage and limited repair range in the existing technology are solved. , achieving high-quality glaze repair effect.

CN119390480AActive Publication Date: 2025-02-07JIANGXI DONGPENG BATHROOM CO LTD +4

Patent Information

Application Number
CN202411531803.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing ceramic glaze defect repair process has problems such as low strength of the repair layer, large firing shrinkage rate, high cracking possibility and limited repair range.

Method used

Using an optimized repair base formulation and process, including mixing waste porcelain powder, coke gem powder, cyanite powder, fuse, zircon silicate and glass fiber, filling it into the U-shaped groove of the pretreated ceramic, and The repaired bottom layer is formed by drying and grinding, and then filled with the repaired surface glaze and calcined by the shuttle chamber kiln.

Benefits of technology

It improves the repair strength, reduces the firing shrinkage rate and cracking possibility, expands the range of repairable defects, makes the repaired glaze surface smooth and has no color difference from the original glaze surface, ensuring aesthetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110643740000191
    Figure BDA0005110643740000191
Patent Text Reader

Abstract

The invention discloses a process for repairing ceramic glaze defects, which comprises the following steps of: A, polishing the defect part of ceramic into a U-shaped groove, and wetting the U-shaped groove to obtain pretreated ceramic; b, the U-shaped groove of the pretreated ceramic is filled with the repairing base material, and the repairing base material is compacted to obtain a repairing bottom layer; c, the repairing bottom layer is sequentially dried and polished, so that the surface of the repairing bottom layer is flush with the surface of the pretreated ceramic; d, the surface of the repairing bottom layer is filled with repairing cover glaze and compacted, and a repairing surface layer is formed; and E, the pretreated ceramic with the repairing surface layer is placed in a shuttle chamber kiln, and repairing is completed. According to the repair process for the ceramic glaze defects, the repair base material formula and the repair process are optimized, so that the firing shrinkage rate and the cracking possibility are reduced, the repair strength is improved, and on the premise of ensuring the repair effect, the repairable defect range can be widened; and the repaired ceramic glaze defect part can be flat and smooth, and the aesthetic property is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic sanitary ware, and in particular to a repairing process for ceramic glaze defects. Background Art

[0002] Nowadays, ceramic sanitary ware (such as wash basins, bathtubs and toilets) has entered thousands of households. With the continuous improvement of the technology of the ceramic sanitary ware industry and the increasing demand of consumers for ceramic sanitary ware, ceramic sanitary ware has gradually developed towards complex appearance and large size. Due to the complex appearance and large size of ceramic sanitary ware, its production process is complicated and the processes are numerous. The glaze of the ceramic sanitary ware is prone to various defects such as cracks or brown eyes to varying degrees, thereby reducing the aesthetics of the ceramic sanitary ware.

[0003] In order to solve the glaze defects of ceramic sanitary ware, it is generally necessary to use a repair process to repair the defects of the ceramic glaze to ensure that the performance of the ceramic sanitary ware is maintained, restore its aesthetics to the greatest extent, and enable the ceramic sanitary ware to continue to play its due value and role.

[0004] The existing repair process mainly uses a single layer of repair glaze as a repair material to repair its defects to obtain a repair layer, but the above repair method is relatively rough, the repair layer is easily worn away quickly, and the repair effect is not good. In order to overcome the above defects, the industry has adopted a repair material composed of a repair base material and a repair glaze to repair the defects of the ceramic glaze. Among them, the repair base material is mainly mixed with raw materials such as bentonite, white pottery mud and gypsum powder, but the strength of the repair base material mixed with the above raw materials is low, so that the strength of the defect after repair is poor and cannot meet the high-quality repair requirements. At the same time, if the calcination temperature of the repair base material is too high, it will cause bubbles and cracks to appear in the repair bottom layer obtained by calcination, affecting the strength after repair. In order to reduce the calcination temperature of the repair base material, a large amount of flux is usually added to the repair base material, such as potassium oxide and sodium oxide, but the addition of a large amount of flux leads to a large firing shrinkage rate of the repair base material, which also makes the repair bottom layer obtained by calcination easy to crack, and the repair strength will also be reduced, further reducing its repair quality. In addition, due to the above-mentioned defects of the repair base material, the repair material can only repair defects with a length of less than 20 mm, a width of less than 1 mm and a depth of less than 1 mm, and the range of defects that can be repaired is very limited. Summary of the invention

[0005] The purpose of the present invention is to propose a repairing process for ceramic glaze defects. By optimizing the formula of the repair base material and the repairing process, it is beneficial to reduce the firing shrinkage rate and the possibility of cracking and improve the repair strength. Under the premise of ensuring the repairing effect, not only can defects with a length of ≤60mm, a width of ≤5mm and a depth of ≤5mm be repaired, thereby increasing the range of repairable defects, but also the repaired ceramic glaze defects can be made smooth and flat, and have no color difference with the rest of the ceramic glaze, thereby ensuring aesthetics.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A process for repairing ceramic glaze defects comprises the following steps:

[0008] A. Grinding the defects of the ceramic into a U-shaped groove, and wetting the U-shaped groove to obtain the pretreated ceramic;

[0009] B. Filling the repair base material into the U-shaped groove of the pretreated ceramic and compacting it to obtain a repair base layer; wherein, calculated by weight, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of coke gem powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate and 0.2-1 part of glass fiber, and the thermal expansion coefficient of the flux block I is (2-3)×10 -6 / ℃;

[0010] C. drying and grinding the repair bottom layer in sequence to make the surface of the repair bottom layer flush with the surface of the pretreated ceramic;

[0011] D. filling the repair glaze on the surface of the repair base layer and compacting it to form a repair surface layer;

[0012] E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, heat the shuttle kiln from room temperature to 1175-1185°C at a heating rate of 10-15°C / min and keep it warm for 23-25h, then cool it down to room temperature at a cooling rate of 10-15°C / min to complete the repair.

[0013] Furthermore, in step B, the repair base material further comprises sodium carboxymethyl cellulose solution, glycerol and a preservative;

[0014] Calculated by mass, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of pyrope powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate, 0.2-1 part of glass fiber, 2-6 parts of sodium carboxymethyl cellulose solution, 0.2-1 part of propylene glycol and 0.2-1 part of preservative.

[0015] Further, in step D, the repair glaze includes 85-95 parts of glaze slurry I, 10-15 parts of glaze slurry II, 2-10 parts of flux block II and 0.2-0.5 parts of glycerol, calculated by weight;

[0016] Calculated by weight, the glaze slurry I includes 15-25 parts of feldspar, 20-30 parts of quartz, 3-5 parts of dolomite, 8-15 parts of wollastonite, 5-10 parts of calcium carbonate, 4-6 parts of kaolin, 3-5 parts of calcined alumina, 1-3 parts of calcined zinc oxide and 8-10 parts of zirconium silicate;

[0017] Calculated by weight, the surface glaze slurry II includes 40-50 parts of feldspar, 15-25 parts of quartz, 20-30 parts of wollastonite and 10-20 parts of calcined zinc oxide.

[0018] Furthermore, the particle sizes of the flux block I and the flux block II are both ≤160 μm;

[0019] Calculated by mass percentage, the chemical composition of the flux block I and the flux block II includes SiO 2 60~68%、Al 2 O 3 6~14%,Fe 2 O 3 0.10~0.50%、TiO 2 0.01~0.05%, CaO 4~12%, MgO 0.15~0.5%, K 2 O 2~5%, Na 2 O 0.5~1.5%、ZrO 2 0.10~0.50%, ZnO 0.20~0.60%, B 2 0 3 8~12% and Ba0 0.30~0.60%, and the rest is loss on ignition.

[0020] Furthermore, the diameter of the glass fiber is ≤30 mm.

[0021] Furthermore, in step B, the thickness of the repair bottom layer is 8 to 10 μm;

[0022] In step D, the thickness of the repair surface layer is 3 to 5 μm.

[0023] Furthermore, the particle size of the coke gemstone powder is ≤200 μm;

[0024] According to the mass percentage, the particle size of the kyanite powder is: after passing through a 200-mesh sieve, the residue is 60-70%;

[0025] According to mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the residue is 0-0.5%.

[0026] Furthermore, the particle size of the waste porcelain powder is ≤200 μm;

[0027] Calculated by mass percentage, the chemical composition of the waste porcelain powder includes SiO 2 65~73%、Al 2 O 3 19~27%,Fe 2 O 3 1~2%、TiO 2 0.01~0.1%, CaO 0.5~1.5%, MgO 0.01~0.05%, K 2 O 2.5~3.5% and Na 2 O 0.5~1%, the rest is loss on ignition.

[0028] Furthermore, the specific steps in step A are: first use a carbon rod vibration pen to grind the defects of the ceramic into a U-shaped groove, blow away the ground ceramic powder with an air gun, and then wipe and moisten the U-shaped groove with a wet towel to obtain pretreated ceramics.

[0029] Furthermore, in step B, the preparation method of the repair base material is: after uniformly mixing the waste porcelain powder, coke sapphire powder, kyanite powder, flux block I and zirconium silicate in the formula amount, an intermediate slurry I is obtained; then, the glass fiber, sodium carboxymethyl cellulose, glycerol and preservative in the formula amount are added to the intermediate slurry I, and the repair base material is obtained after uniform stirring;

[0030] In step D, the preparation method of the repair glaze is: after evenly mixing the formulated amount of glaze slurry I, glaze slurry II and flux block II, an intermediate slurry II is obtained; and after evenly mixing the formulated amount of propylene glycol into the intermediate slurry II, a repair glaze is obtained.

[0031] The technical solution provided by the embodiments of the present application may have the following beneficial effects:

[0032] 1. Before filling the repair glaze, first fill the repair base material into the U-shaped groove of the pretreated ceramic and compact it to ensure that the repair base material fully fills the U-shaped groove. On the one hand, it reduces the gap between the repair base material and the pretreated ceramic body to ensure the close combination of the two. On the other hand, it is helpful to avoid the presence of bubbles or gaps in the repair base material after filling, which causes cracks after calcination and affects the repair effect. In addition, the repair base material provided by this scheme has high strength, and the volume shrinkage rate of the repair base material after calcination is small and the possibility of cracking is extremely low. It is not only beneficial to improve the repair effect, but also can repair defects with a length of ≤60mm, a width of ≤5mm and a depth of ≤5mm, thereby increasing the range of repairable defects.

[0033] 2. Use shuttle kiln for calcination, specifically: let the shuttle kiln rise from room temperature to 1175-1185℃ at a heating rate of 10-15℃ / min and keep it warm for 23-25h, then cool it down to room temperature at a cooling rate of 10-15℃ / min to obtain ceramics with a repair layer and complete the repair. The use of low calcination temperature, long calcination time, low heating rate and low cooling rate can effectively alleviate the influence of thermal stress on the repair material, reduce the wear and cracks of the repair layer, so that the defects of the re-fired ceramic sanitary ware after repair are smooth and there is no obvious color difference with the original product. At the same time, compared with the simple structure of the tunnel kiln, the structure of the shuttle kiln is more complicated, with many channels and layers inside. When the pre-treated ceramic with a repair surface layer enters the kiln, it needs to go through a series of stays, rests and heating processes to complete the calcination, which is more conducive to alleviating the influence of thermal stress on the repair material and ensuring the repair effect. DETAILED DESCRIPTION

[0034] The present technical solution provides a repair process for ceramic glaze defects, comprising the following steps:

[0035] A. Grinding the defects of the ceramic into a U-shaped groove, and wetting the U-shaped groove to obtain the pretreated ceramic;

[0036] B. Filling the repair base material into the U-shaped groove of the pretreated ceramic and compacting it to obtain a repair base layer; wherein, calculated by weight, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of coke gem powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate and 0.2-1 part of glass fiber, and the thermal expansion coefficient of the flux block I is (2-3)×10 -6 / ℃;

[0037] C. drying and grinding the repair bottom layer in sequence to make the surface of the repair bottom layer flush with the surface of the pretreated ceramic;

[0038] D. filling the repair glaze on the surface of the repair base layer and compacting it to form a repair surface layer;

[0039] E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, heat the shuttle kiln from room temperature to 1175-1185°C at a heating rate of 10-15°C / min and keep it warm for 23-25h, then cool it down to room temperature at a cooling rate of 10-15°C / min to complete the repair.

[0040] In order to solve the defects of poor repair effect and limited repair range in the prior art, the present technical scheme proposes a repair process for ceramic glaze defects, including five steps of A (pretreatment), B (filling repair base material), C (grinding treatment), D (filling repair surface glaze) and E (calcining in the kiln), and then the ceramic defects are repaired by innovating the formula of the repair base material combined with the repair process. The whole repair process is simple and easy to operate, which is beneficial to reduce the firing shrinkage rate and the possibility of cracking and improve the repair strength. Under the premise of ensuring the repair effect, not only the defects with a length of ≤60mm, a width of ≤5mm and a depth of ≤5mm can be repaired, thereby increasing the range of repairable defects, but also the defects of the repaired ceramic glaze surface can be made flat and smooth, and there is no color difference with the rest of the ceramic glaze surface, thereby ensuring the aesthetics after repair.

[0041] Specifically, since the cracks or brown eyes at the defects of the ceramic glaze are generally small, if the repair base material is directly filled thereon, the filling effect of the repair base material will be poor, and it will be difficult to ensure the repair effect. Therefore, the technical solution first grinds the defects of the ceramic into a U-shaped groove, which is conducive to the subsequent repair and filling work. At the same time, after the grinding is completed, the U-shaped groove is moistened so that the repair base material can effectively adhere to the U-shaped groove, which is conducive to ensuring the repair effect.

[0042] Secondly, before filling the repair glaze, the technical scheme first fills the repair base material into the U-shaped groove of the pretreated ceramic and compacts it to ensure that the repair base material fully fills the U-shaped groove. On the one hand, it reduces the gap between the repair base material and the pretreated ceramic body to ensure the close combination of the two. On the other hand, it is beneficial to avoid the presence of bubbles or gaps in the repair base material after filling, which causes cracks after calcination and affects the repair effect. In addition, the repair base material provided by the present scheme has high strength, and the volume shrinkage rate of the repair base material after calcination is small and the possibility of cracking is extremely low. It is not only beneficial to improve the repair effect, but also can repair defects with a length of ≤60mm, a width of ≤5mm and a depth of ≤5mm, thereby increasing the range of repairable defects.

[0043] Furthermore, the repair base material is mainly made of a mixture of raw materials such as bentonite, white pottery mud and gypsum powder, but the strength of the above raw materials is relatively low, so that the strength of the mixed repair base material is relatively low, and the strength of the defect after repair is relatively poor, which cannot meet the high-quality repair requirements. The repair base material of the present technical solution includes waste porcelain powder, blue topaz powder, pyrope powder, flux block, zirconium silicate, and glass fiber. Among them, waste porcelain powder is a powder formed by grinding ceramic waste, so it has a high strength itself, thus giving the repair base material high strength; glass fiber is a fibrous material formed by a fiberization process after high-temperature melting of glass raw materials, which has extremely high strength and can also significantly improve the strength of the repair base material; pyrope powder is a powder obtained by grinding, drying, crushing and screening pyrope, and its main components are high-strength aluminum oxide and silicon dioxide, which also give the repair base material high strength; zirconium silicate is added to the repair base material formula, which is also conducive to improving the strength of the repair base material. Therefore, in the formula of the repair base material of the technical solution, waste porcelain powder, glass fiber, pyrope powder and zirconium silicate are combined to make the repair base material have high strength, and the repair bottom layer after calcination has high strength, meeting the high-quality repair requirements. In addition, zirconium silicate is also conducive to improving the whiteness of the repair base material, avoiding the repair bottom layer from being too dark in color and affecting the overall decorative effect of the repaired ceramic sanitary ware.

[0044] Furthermore, the shape of glass fiber is generally continuous fiber, and its unique fiber structure can form a stable skeleton framework in the material, which not only enables it to effectively resist the volume shrinkage of the flux components in the repair base material after high-temperature calcination, but also provides skeleton support for the repair base material to avoid high-temperature calcination cracks in the repair base material.

[0045] Kyanite powder will expand in volume during high-temperature calcination. Its expansion under high-temperature conditions can not only effectively offset the loose stacking produced during the filling process of the repair base material, but also offset the volume shrinkage of the flux components in the repair base material after high-temperature calcination, thereby eliminating the repair cracks caused by stress and reducing the possibility of crack expansion, greatly improving the repair range of the repair base material.

[0046] The coke gem powder can enter the pores and cracks of the repair base material, effectively filling these spaces and improving the density and overall performance of the repair base material. At the same time, the coke gem powder has a certain volume stability at high temperatures. When the repair base material is sintered at high temperatures, the coke gem powder can effectively reduce the volume shrinkage of the repair base material after calcination.

[0047] Waste porcelain powder can enter the pores and cracks of the repair base material, effectively filling these spaces and improving the density and overall performance of the repair base material. At the same time, since waste porcelain powder is a clinker calcined at high temperature, its volume stability is relatively high, and the particles of waste porcelain powder can form a stable bond, which is conducive to reducing the stress concentration and crack expansion caused by material shrinkage during the calcination of the repair base material, thereby improving the overall stability of the repair base material. In addition, waste porcelain powder is mainly used as a skeleton material, and its main characteristics are consistent with the pre-treated ceramic body, which is conducive to the close bonding of the two and is not easy to peel off.

[0048] At the same time, the repair base material formula also includes flux block I, which can reduce the sintering temperature of the repair base material, so that the repair base material can be calcined at a lower temperature to form a eutectic glass body, achieve a vitrification effect and closely combine with the pretreated ceramic body, thereby improving the bonding firmness; at the same time, the thermal expansion coefficient of the flux block I in the technical solution is (2-3)×10 -6 / ℃, compared with the existing flux potassium oxide and sodium oxide, its expansion coefficient is extremely low, which greatly reduces the volume shrinkage of the repair base material after calcination, which not only reduces the possibility of cracking after calcination, but also helps to increase the range of repairable defects. In addition, in this technical solution, the addition amount of flux block I is limited to 5 to 15 parts, so that the repair base material can be fully calcined and vitrified at a lower addition amount, ensuring its bonding firmness with the pre-treated ceramic body, and at the same time helping to reduce the volume shrinkage after calcination.

[0049] If the calcination temperature of the repair base material is too high, it will cause the repair bottom layer obtained by calcination to be prone to bubbles and cracks, affecting the strength after repair. In order to reduce the calcination temperature of the repair base material, a large amount of fluxing agents, such as potassium oxide and sodium oxide, are usually added to the repair base material, but the addition of a large amount of fluxing agents causes the sintering shrinkage of the repair base material to be large, and the repair bottom layer obtained by calcination is also prone to cracking, and the repair strength will also be reduced, further reducing its repair quality. Therefore, in the technical scheme, the volume shrinkage and cracking possibility of the repair base material after calcination are greatly reduced by the mutual cooperation of glass fiber, kyanite powder, waste porcelain powder, coke gem powder and fluxing block, and the thermal expansion coefficient and addition amount of fluxing block I are limited, which is not only conducive to improving the repair effect, but also can repair the defects of length ≤60mm, width ≤5mm and depth ≤5mm, improve the repairable defect range, solve the technical defects of the repair base material in the prior art that the volume shrinkage is too large after calcination, it is easy to crack, resulting in poor repair strength, and the limited repair defect range.

[0050] In addition, the main components of coke gem powder are alumina and silicon dioxide with high hardness and high chemical stability, which give the coke gem powder chemical stability and high wear resistance, which is conducive to extending the service life of the repair layer. In addition, coke gem powder will also produce mullite during the high-temperature calcination process, which is conducive to improving the thermal shock resistance of the repair base material.

[0051] Before filling the repair glaze, the technical solution also needs to dry and grind the repair base layer in sequence to make the surface of the pretreated ceramics flush. The drying step is conducive to the initial solidification of the repair base layer to avoid it being easily polished away during the subsequent polishing process, which increases the difficulty of polishing. At the same time, through the polishing step, on the one hand, the burrs, oil stains, dust and other impurities on the surface of the repair base layer can be removed, so that the repair surface layer formed by the repair glaze can be better combined with the repair base layer. On the other hand, polishing makes the surface of the repair base layer flush with the surface of the pretreated ceramic, which can reduce the obvious degree of the repair marks. The repaired ceramic sanitary ware is visually closer to the original state, which improves the concealment and aesthetics of the repair. In addition, since the surface of the repair base layer is smooth and free of impurities after polishing, the application of the repair glaze is smoother, reducing the problem of repair difficulties and reduced efficiency due to the uneven surface of the repair base layer or the presence of impurities.

[0052] Secondly, the repair glaze is filled on the surface of the repair base and compacted to form a repair surface layer. The repair glaze can restore the original color and texture of the ceramic sanitary ware, making the defects of the repaired ceramic glaze visually consistent with the rest of the parts, and it is difficult to detect the repair marks. At the same time, after the repair glaze is filled and compacted, the surface is smooth and flat, perfectly integrated with the rest of the ceramic glaze, improving the overall aesthetics; in addition, the repair glaze can protect the repair base from erosion by the external environment and form a solid protective layer, which improves the durability of the repaired ceramic.

[0053] Finally, in the prior art, tunnel kilns are generally used for calcination, but the calcination temperature of tunnel kilns is high, the calcination time is short, and the heating rate is fast, resulting in large thermal stress during the calcination process, which easily causes cracks in the calcined ceramic sanitary ware, making it difficult to ensure the repair effect even if a repair base material with low shrinkage and low cracking possibility is used. Therefore, the shuttle kiln is used for calcination in this technical solution, specifically: the shuttle kiln is heated from room temperature to 1175-1185°C at a heating rate of 10-15°C / min and kept warm for 23-25h, and then cooled to room temperature at a cooling rate of 10-15°C / min to obtain a ceramic with a repair layer and complete the repair. The use of low calcination temperature, long calcination time, low heating rate and low cooling rate can effectively alleviate the influence of thermal stress on the repair material, reduce the wear and cracks of the repair layer, so that the defects of the re-fired ceramic sanitary ware after repair are smooth and flat, and there is no obvious color difference with the original product. At the same time, compared with the simple structure of the tunnel kiln, the shuttle kiln has a more complex structure with many channels and layers inside. When the pretreated ceramics with a repair surface layer enter the kiln, they need to go through a series of dwelling, resting and heating processes before calcination can be completed, which is more conducive to alleviating the impact of thermal stress on the repair material and ensuring the repair effect.

[0054] Therefore, this technical solution uses an innovative formula of repair base material to replace the existing technology of using a mixture of bentonite, white pottery mud, gypsum powder and other raw materials to repair ceramic glaze defects. Combined with the repair process, the repair base material has the characteristics of high strength, low volume shrinkage and low cracking possibility, and the shuttle kiln calcination process is not easy to produce cracks. Under the premise of ensuring the repair effect, not only can defects with a length of ≤60mm, a width of ≤5mm and a depth of ≤5mm be repaired, thereby increasing the range of repairable defects, but also the repaired ceramic glaze defects can be made smooth and flat, and have no color difference with the rest of the ceramic glaze, ensuring aesthetics.

[0055] In addition, the repair process of this scheme is efficient and simple, the repair difficulty is low and the production efficiency is high. The color of the obtained repair layer is close to the ceramic glaze surface, and it can be widely used in the repair of ceramic glaze defects.

[0056] Further, in step B, the repair base material also includes sodium carboxymethyl cellulose solution, glycerol and a preservative;

[0057] Calculated by mass, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of pyrope powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate, 0.2-1 part of glass fiber, 2-6 parts of sodium carboxymethyl cellulose solution, 0.2-1 part of propylene glycol and 0.2-1 part of preservative.

[0058] In a preferred embodiment of the present technical solution, the repair base material also includes sodium carboxymethyl cellulose solution, glycerol and preservatives, wherein the sodium carboxymethyl cellulose solution can increase the adhesion of the repair base material, reduce the drying shrinkage of the repair base material, prevent the occurrence of defects such as glaze rolling and glaze deficiency, thereby improving the filling effect, which is conducive to improving the range of defects that can be repaired; glycerol can ensure the moisture retention of the repair base material, prevent the repair base material from drying quickly and causing fine lines or cracks, and improve the plasticity and ductility of the repair base material; the preservative can prevent the repair base material from being invaded by microorganisms and molds during processing and use, thereby extending the quality and service life of the repair base material. Therefore, in the present technical solution, by adding sodium carboxymethyl cellulose solution, glycerol and preservatives to the repair base material formula, it is not only conducive to extending the quality and service life of the repair base material, but also can avoid cracks in the drying process of the repair base material, ensure its filling effect, and improve the range of defects that can be repaired.

[0059] Furthermore, calculated by mass, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of charcoal gemstone, 25-35 parts of kyanite, 5-15 parts of flux block I, 2-10 parts of zirconium silicate, 0.2-1 part of glass fiber, 2-6 parts of sodium carboxymethyl cellulose solution, 0.2-1 part of propylene glycol and 0.2-1 part of preservative. By adjusting the added amount of each raw material in the formula of the repair base material, it is beneficial to achieve better performance of the repair base material and ensure the repair effect.

[0060] Preferably, the preservative includes at least one of benzoic acid, sodium benzoate, sorbic acid and potassium sorbate. Benzoic acid, sodium benzoate, sorbic acid and potassium sorbate all have good preservative effects, and adding them into the formula is beneficial to prevent the repair base material from being damaged by microorganisms and molds during processing and use, thereby extending the quality and service life of the repair base material.

[0061] Preferably, calculated by mass percentage, the sodium carboxymethyl cellulose solution includes 95-97% sodium carboxymethyl cellulose and 3-5% water.

[0062] Further, in step D, the repair glaze includes 85-95 parts of glaze slurry I, 10-15 parts of glaze slurry II, 2-10 parts of flux block II and 0.2-0.5 parts of glycerol, calculated by weight.

[0063] Calculated by weight, the glaze slurry I includes 15-25 parts of feldspar, 20-30 parts of quartz, 3-5 parts of dolomite, 8-15 parts of wollastonite, 5-10 parts of calcium carbonate, 4-6 parts of kaolin, 3-5 parts of calcined alumina, 1-3 parts of calcined zinc oxide and 8-10 parts of zirconium silicate;

[0064] Calculated by weight, the surface glaze slurry II includes 40-50 parts of feldspar, 15-25 parts of quartz, 20-30 parts of wollastonite and 10-20 parts of calcined zinc oxide.

[0065] In a preferred embodiment of the present technical solution, the raw materials for the repair glaze include glaze slurry I, glaze slurry II, flux block II and propylene glycol, wherein glaze slurry I is used to improve the hardness, strength, wear resistance and corrosion resistance of the repair glaze, and glaze slurry II is used to improve the whiteness and glossiness of the repair glaze. The performance of the repair glaze is ensured by the mutual cooperation of glaze slurry I and glaze slurry II.

[0066] In addition, the raw materials of the repair glaze also include flux block II and propylene glycol. Flux block II is an important additive in the repair glaze, which can reduce the melting temperature of the repair glaze, making the repair glaze easier to combine with the repair base material and the pretreated ceramic body; propylene glycol mainly plays the role of wetting and adjusting the viscosity of the glaze slurry, which can make the repair glaze slurry easier to apply and evenly, and help the repair glaze to form a uniform repair surface layer after calcination, thereby ensuring the repair effect.

[0067] Furthermore, calculated by mass, the repair glaze includes 85-95 parts of glaze slurry I, 10-15 parts of glaze slurry II, 2-10 parts of flux block II and 0.2-0.5 parts of propylene glycol. By adjusting the added amount of each raw material in the repair glaze formula, it is beneficial to achieve the best performance of the repair base material and ensure the repair effect.

[0068] It is further described that the particle sizes of the flux block I and the flux block II are both ≤160 μm;

[0069] Calculated by mass percentage, the chemical composition of the flux block I and the flux block II includes SiO 2 60~68%、Al 2 O 3 6~14%,Fe 2 O 3 0.10~0.50%、TiO 2 0.01~0.05%, CaO 4~12%, MgO 0.15~0.5%, K 2 O 2~5%, Na 2 O 0.5~1.5%、ZrO 2 0.10~0.50%, ZnO 0.20~0.60%, B 2 0 3 8~12% and Ba0 0.30~0.60%, and the rest is loss on ignition.

[0070] If the particle size of flux blocks I and II is too large, the glass phase will increase, and the local stress will be uneven during the calcination process, affecting the repair effect; if the particle size of flux blocks I and II is too small, the difficulty of their processing and production will be increased, the production efficiency will be reduced, and the production cost will be increased. Therefore, in a preferred embodiment of the present technical solution, the particle size of flux blocks I and II is limited to less than 160μm, which is beneficial to ensure the fluxing effect and repair effect at a lower production cost.

[0071] Furthermore, the chemical composition of flux block I and flux block II includes SiO 2 、Al 2 O 3 , Fe 2 O 3 、TiO 2 , CaO, MgO, K 2 O、Na 2 O, ZrO 2 , ZnO, B 2 0 3 and Ba0, where K 2 O and Na 2 O can broaden the firing range, has good stability, and reduces melting temperature and high temperature viscosity; B 2 0 3 It can play a role in fluxing, reduce the thermal expansion coefficient, and improve the thermal shock resistance, which is conducive to matching the performance of the pre-treated ceramic itself and avoiding bumps during calcination; in addition, B 2 0 3 It can also reduce K 2 O and Na 2 The addition of O ensures a good fluxing effect while also having an extremely low thermal expansion coefficient; CaO can reduce the viscosity during high-temperature melting, enhance the bonding strength of the body and glaze, and prevent the occurrence of glaze baldness; SiO 2 Can improve high temperature viscosity, strength and calcination temperature; Al 2 O 3 It can improve the high temperature viscosity, initial melting point, hardness, acid and alkali resistance and chemical stability; MgO can increase the melting temperature range at high temperature; K 2 O and Na 2 O can broaden the sintering range, has good stability, and reduces the melting temperature and high temperature viscosity.

[0072] Therefore, in the present technical scheme, the chemical composition of flux block I and flux block II is optimized and the addition amount of each chemical component is limited to ensure that flux block I and flux block II not only have a good fluxing effect but also have an extremely low thermal expansion coefficient; in addition, flux block I and flux block II are also beneficial to improving the thermal shock resistance, matching the performance of the pretreated ceramic itself, avoiding bumps during calcination, and ensuring the repair effect.

[0073] It is further specified that the diameter of the glass fiber is ≤30 mm.

[0074] In a preferred embodiment of the present technical solution, the diameter of the glass fiber is limited to within 30 mm, so that it can not only increase the mechanical strength and tensile strength of the repair base material, but also fill the calcination cracks that appear during the calcination process of the repair base material, reduce the possibility of cracking of the repair base layer, and ensure the repair effect.

[0075] Further, in step B, the thickness of the repair bottom layer is 8 to 10 μm;

[0076] In step D, the thickness of the repair surface layer is 3 to 5 μm.

[0077] The thickness of the repair bottom layer is 8-10 μm. If the thickness of the repair bottom layer is too thick, it will increase the difficulty of grinding and reduce the repair efficiency; if the thickness of the repair bottom layer is too thin, the strength and hardness after repair will be insufficient, affecting its service life. Therefore, in a preferred embodiment of the present technical solution, the thickness of the repair bottom layer is limited to 8-10 μm, which is conducive to improving the repair efficiency and extending the service life.

[0078] Furthermore, if the thickness of the repair surface layer is too thick, it is easy to increase the repair cost, and it is also easy to cause a height difference between the defective part of the repaired ceramic glaze and the surrounding area, affecting the repair effect; if the thickness of the repair surface layer is too thin, the protection of the repair bottom layer is reduced, and it is easy to be worn, which also affects the repair effect. Therefore, in a preferred embodiment of the present technical solution, the thickness of the repair surface layer is limited to 3 to 5 μm to ensure the repair effect.

[0079] It is further stated that the particle size of the coke gemstone powder is ≤200 μm;

[0080] According to the mass percentage, the particle size of the kyanite powder is: after passing through a 200-mesh sieve, the residue is 60-70%;

[0081] According to mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the residue is 0-0.5%.

[0082] If the particle size of the coke gem powder is too large, the mullite crystal phase produced by the coke gem powder during the high-temperature calcination process will increase locally, causing uneven shrinkage of the repair base material.

[0083] If the particle size of kyanite powder is too large, the water absorption rate of the repair base material will increase and the flexural strength will decrease; if the particle size of kyanite powder is too small, it will easily lose its high-temperature expansion properties, making the repair base material prone to cracking during calcination.

[0084] If the particle size of zirconium silicate is too small, its hardness and strength will be reduced, thereby affecting the relevant properties of the repair base material; if the particle size of zirconium silicate is too large, the porosity of the repair base material will increase, making it more likely to crack.

[0085] Therefore, in a preferred embodiment of the technical solution, the particle sizes of the sapphire powder, kyanite powder and zirconium silicate are limited to ensure the performance of the repair base material and improve the repair effect.

[0086] It is further stated that the particle size of the waste porcelain powder is ≤200 μm;

[0087] Calculated by mass percentage, the chemical composition of the waste porcelain powder includes SiO 2 65~73%、Al 2 O 3 19~27%,Fe 2 O 3 1~2%、TiO 2 0.01~0.1%, CaO 0.5~1.5%, MgO 0.01~0.05%, K 2 O 2.5~3.5% and Na 2 O 0.5~1%, the rest is loss on ignition.

[0088] In a preferred embodiment of the present technical solution, by optimizing the particle size and composition of the waste porcelain powder, it is ensured that the waste porcelain powder can not only fully fill the gaps in the repair base material and reduce its volume shrinkage during the calcination process, but also help to improve the hardness and strength of the repair base material.

[0089] To further illustrate, the specific steps in step A are: first use a carbon rod vibration pen to grind the defects of the ceramic into a U-shaped groove, blow away the ground ceramic powder with an air gun, and then wipe and moisten the U-shaped groove with a wet towel to obtain pretreated ceramics.

[0090] Since the carbon rod has high hardness, the hardness and vibration of the carbon rod are used to grind and shape the ceramic surface, so that the defects of the ceramic are polished into a regular U-shaped groove, which is helpful for subsequent repair and filling work. The ceramic powder is blown away by an air gun that can generate high-speed airflow to ensure the smooth progress of subsequent steps. In addition, there may still be tiny powder particles or stains left on the surface of the U-shaped groove after grinding. In order to obtain a clean and smooth repair surface, wipe it with a wet towel to absorb and take away the tiny particles or stains on the surface, ensuring that the surface of the U-shaped groove is cleaner and smoother. At the same time, the wet towel can also moisten the U-shaped groove, which is conducive to subsequent filling and repair work, ensuring that the repaired ceramic cleaner has better appearance and performance.

[0091] Further, in step B, the preparation method of the repair base material is: after uniformly mixing the waste porcelain powder, coke sapphire powder, kyanite powder, flux block I and zirconium silicate in the formula amount, an intermediate slurry I is obtained; then, the glass fiber, sodium carboxymethyl cellulose, propylene glycol and preservative in the formula amount are added to the intermediate slurry I, and the repair base material is obtained after uniform stirring;

[0092] In step D, the preparation method of the repair glaze is: after evenly mixing the formulated amount of glaze slurry I, glaze slurry II and flux block II, an intermediate slurry II is obtained; and after evenly mixing the formulated amount of propylene glycol into the intermediate slurry II, a repair glaze is obtained.

[0093] In a preferred embodiment of the present technical scheme, an intermediate slurry I is obtained by uniformly mixing the formulated amounts of waste porcelain powder, coke powder, kyanite powder, flux block I and zirconium silicate; then the formulated amounts of glass fiber, sodium carboxymethyl cellulose, propylene glycol and preservative are added to the intermediate slurry I, and stirred evenly to obtain a repair base material; the formulated amounts of glaze slurry I, glaze slurry II and flux block are mixed evenly to obtain an intermediate slurry II; then the formulated amount of propylene glycol is added to the intermediate slurry II and mixed evenly to obtain a repair glaze. The preparation method is simple and easy to operate, ensuring that the obtained repair base material has high strength, and at the same time its calcination shrinkage and cracking possibility are extremely low, and the obtained repair glaze has strong wear resistance, corrosion resistance, whiteness and glossiness. On the premise of ensuring the repair effect, it not only increases the range of repairable defects, but also makes the defects on the repaired ceramic glaze surface smooth and smooth, and has no color difference with the rest of the ceramic glaze surface, ensuring aesthetics. It should be noted that the intermediate slurry II is obtained by first evenly mixing the formulated amounts of glaze slurry I, glaze slurry II, glaze slurry and flux block II, which can ensure that the glaze slurry I, glaze slurry II and flux block II are fully integrated to form a stable intermediate slurry II; the glaze slurry I, glaze slurry II and flux block II are added after they are evenly mixed to ensure that propylene glycol is evenly distributed in the repair glaze, thereby giving full play to its moisturizing properties, ductility and crack resistance.

[0094] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0095] Performance Test:

[0096] Repair effect: Observe the repair effect of the defects on the ceramic glaze surface with naked eyes;

[0097] Thermal shock resistance: Place the repaired ceramic sanitary ware into a furnace preheated to 110°C, keep warm for 20 minutes, then quench in room temperature water for 3 minutes. After drying, observe whether there are cracks in the repair layer.

[0098] Firing shrinkage rate: Place the repair layer in a beaker and soak it in 100℃ boiling water for 15 minutes. Take out the repair layer and wait until it is completely dry. Use a caliper or ruler to measure the length of the repair layer before and after water immersion. Divide the difference in length of the repair layer before and after water immersion by the length before water immersion, and then multiply by 100% to obtain the percentage of boiling water shrinkage rate.

[0099] Example Group

[0100] Example 1

[0101] A. First, a carbon rod vibration pen is used to grind the defects of the ceramic with a length of 55 mm, a width of 4 mm and a depth of 4.5 mm into a U-shaped groove. After blowing away the polished ceramic powder with an air gun, the U-shaped groove is wiped and moistened with a wet towel to obtain pre-treated ceramics;

[0102] B. Fill the repair base material into the U-shaped groove of the pretreated ceramic and compact it to obtain the repair base layer; wherein, calculated by weight, the repair base material includes 30 parts of waste porcelain powder, 25 parts of pyrope powder, 25 parts of kyanite powder, 10 parts of flux block I, 10 parts of zirconium silicate, 0.8 parts of glass fiber, 4 parts of sodium carboxymethyl cellulose solution, 0.2 parts of glycerol and 0.2 parts of sodium benzoate; the thickness of the repair base layer is 10 μm; the particle size of flux block I is 150 μm, and the thermal expansion coefficient of flux block I is 2.2×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block I includes SiO 2 65%、Al 2 O 3 6%, Fe 2 O 3 0.50%, TiO 2 0.01%, CaO 12%, MgO 0.5%, K 2 O 3%, Na 2 O 1.0%, ZrO 2 0.10%, ZnO 0.40%, B 2 0 3 10% and Ba00.30%, and the rest is the loss on ignition; the diameter of the glass fiber is 25mm; the particle size of the pyrope powder is 200μm; according to the mass percentage, the particle size of the kyanite powder is: passing through a 200-mesh sieve, the sieve residue is 60-70%; according to the mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the sieve residue is 0-0.5%; the particle size of the waste porcelain powder is 180μm; according to the mass percentage, the chemical composition of the waste porcelain powder includes SiO 2 68%, Al 2 O 3 20%, Fe 2 O 3 2%, TiO 20.1%, CaO 1.5%, MgO 0.05%, K 2 O3.5% and Na 2 O 1%, the rest is loss on ignition;

[0103] C. Dry and polish the repair base layer in sequence to make the surface of the repair base layer flush with the surface of the pre-treated ceramic;

[0104] D. Fill the repair glaze on the surface of the repair base and compact it to form a repair surface layer; the thickness of the repair surface layer is 3-5 μm; calculated by weight, the repair glaze includes 85 parts of glaze slurry I, 15 parts of glaze slurry II, 3 parts of fluxing block II and 0.2 parts of propylene glycol; calculated by weight, the glaze slurry I includes 15 parts of feldspar, 30 parts of quartz, 5 parts of dolomite, 10 parts of wollastonite, 10 parts of calcium carbonate, 4 parts of kaolin, 3 parts of calcined alumina, 2 parts of calcined zinc oxide and 8 parts of zirconium silicate; calculated by weight, the glaze slurry II includes 40 parts of feldspar, 25 parts of quartz, 30 parts of wollastonite and 20 parts of calcined zinc oxide; the particle size of fluxing block II is 150 μm, and the thermal expansion coefficient of fluxing block II is 2.2×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block II includes SiO 2 65%、Al 2 O 3 6%, Fe 2 O 3 0.50%, TiO 2 0.01%, CaO 12%, MgO 0.5%, K 2 O3%, Na 2 O 1.0%, ZrO 2 0.10%, ZnO 0.40%, B 2 0 3 10% and Ba0 0.30%, the rest is loss on ignition; the diameter of the glass fiber is 25mm;

[0105] E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, heat the shuttle kiln from room temperature to 1175-1185°C at a heating rate of 10-15°C / min and keep it warm for 23-25h, then cool it down to room temperature at a cooling rate of 10-15°C / min to complete the repair.

[0106] Example 2

[0107] A. First, a carbon rod vibration pen is used to grind the defects of the ceramic with a length of 60 mm, a width of 5 mm and a depth of 5 mm into a U-shaped groove. After blowing away the polished ceramic powder with an air gun, the U-shaped groove is wiped and moistened with a wet towel to obtain pre-treated ceramics;

[0108] B. Fill the repair base material into the U-shaped groove of the pretreated ceramic and compact it to obtain the repair base layer; wherein, calculated by weight, the repair base material includes 35 parts of waste porcelain powder, 15 parts of pyrope powder, 35 parts of kyanite powder, 15 parts of flux block I, 2 parts of zirconium silicate, 1 part of glass fiber, 2 parts of sodium carboxymethyl cellulose solution, 0.2 parts of glycerol and 0.8 parts of benzoic acid; the thickness of the repair base layer is 10 μm; the particle size of flux block I is 140 μm, and the thermal expansion coefficient of flux block I is 2×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block I includes SiO 2 68%, Al 2 O 3 14%, Fe 2 O 3 0.10%, TiO 2 0.05%, CaO 8%, MgO 0.15%, K 2 O 5%, Na 2 O 1.0%, ZrO 2 0.50%, ZnO 0.40%, B 2 0 3 10% and BaO 0.5%, the rest is loss on ignition; the diameter of the glass fiber is 25mm; the particle size of the pyrope powder is 170μm; according to the mass percentage, the particle size of the kyanite powder is: passing through a 200-mesh sieve, the sieve residue is 60-70%; according to the mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the sieve residue is 0-0.5%; the particle size of the waste porcelain powder is 180μm; according to the mass percentage, the chemical composition of the waste porcelain powder includes SiO 2 73%, Al 2 O 3 19%, Fe 2 O 3 2%, TiO 2 0.1%, CaO 0.5%, MgO 0.03%, K 2 O 3% and Na 2 O 1%, the rest is loss on ignition;

[0109] C. Dry and polish the repair base layer in sequence to make the surface of the repair base layer flush with the surface of the pre-treated ceramic;

[0110] D. Fill the repair glaze on the surface of the repair base and compact it to form a repair surface layer; the thickness of the repair surface layer is 3μm; calculated by weight, the repair glaze includes 95 parts of glaze slurry I, 12 parts of glaze slurry II, 4 parts of fluxing block II and 0.4 parts of propylene glycol; calculated by weight, the raw materials of glaze slurry I include 20 parts of feldspar, 30 parts of quartz, 4 parts of dolomite, 10 parts of wollastonite, 8 parts of calcium carbonate, 4 parts of kaolin, 5 parts of calcined alumina, 3 parts of calcined zinc oxide and 10 parts of zirconium silicate; calculated by weight, the glaze slurry II includes 50 parts of feldspar, 15 parts of quartz, 25 parts of wollastonite and 15 parts of calcined zinc oxide; the particle size of fluxing block II is 140μm, and the thermal expansion coefficient of fluxing block II is 2×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block II includes SiO 2 68%, Al 2 O 3 14%, Fe 2 O 3 0.10%, TiO 2 0.05%, CaO 8%, MgO 0.15%, K 2 O5%, Na 2 O 1.0%, ZrO 2 0.50%, ZnO 0.40%, B 2 0 3 10% and Ba0 0.5%, the rest is loss on ignition;

[0111] E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, raise the temperature from room temperature to 1175-1185°C at a heating rate of 15°C / min and keep it warm for 25 hours, then cool it down to room temperature at a cooling rate of 10°C / min to complete the repair.

[0112] Example 3

[0113] A. First, a carbon rod vibration pen is used to grind the defects of the ceramic with a length of 50 mm, a width of 5 mm and a depth of 4 mm into a U-shaped groove. After blowing away the polished ceramic powder with an air gun, the U-shaped groove is wiped and moistened with a wet towel to obtain pre-treated ceramics;

[0114] B. Fill the repair base material into the U-shaped groove of the pretreated ceramic and compact it to obtain the repair base layer; wherein, calculated by weight, the repair base material includes 40 parts of waste porcelain powder, 18.2 parts of pyrope powder, 30 parts of kyanite powder, 5 parts of flux block I, 5 parts of zirconium silicate, 0.2 parts of glass fiber, 6 parts of sodium carboxymethyl cellulose solution, 0.6 parts of glycerol and 1 part of sorbic acid; the thickness of the repair base layer is 9 μm; the particle size of flux block I is 130 μm, and the thermal expansion coefficient of flux block I is 2.5×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block I includes SiO 2 60%、Al 2 O 3 14%, Fe 2 O 3 0.50%, TiO 2 0.05%, CaO8%, MgO 0.30%, K 2 O 5%, Na 2 O 1.0%, ZrO 2 0.30%, ZnO 0.60%, B 2 0 3 8% and BaO 0.50%, and the rest is the loss on ignition; the diameter of the glass fiber is 20mm; the particle size of the coke gem powder is 150μm; according to the mass percentage, the particle size of the kyanite powder is: passing through a 200-mesh sieve, the sieve residue is 60-70%; according to the mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the sieve residue is 0-0.5%; the particle size of the waste porcelain powder is 160μm; according to the mass percentage, the chemical composition of the waste porcelain powder includes SiO 2 70%、Al 2 O 3 22%, Fe 2 O 3 2%, TiO 2 0.08%, CaO 0.5%, MgO 0.03%, K 2 O 3.0% and Na 2 O0.8%, the rest is loss on ignition;

[0115] C. Dry and polish the repair base layer in sequence to make the surface of the repair base layer flush with the surface of the pre-treated ceramic;

[0116] D. Fill the repair glaze on the surface of the repair base and compact it to form a repair surface layer; the thickness of the repair surface layer is 4 μm; calculated by weight, the repair glaze includes 90 parts of glaze slurry I, 10 parts of glaze slurry II, 10 parts of fluxing block II and 0.5 parts of propylene glycol; calculated by weight, the glaze slurry I includes 25 parts of feldspar, 20 parts of quartz, 4 parts of dolomite, 8 parts of wollastonite, 10 parts of calcium carbonate, 6 parts of kaolin, 5 parts of calcined alumina, 2 parts of calcined zinc oxide and 9 parts of zirconium silicate; calculated by weight, the glaze slurry II includes 45 parts of feldspar, 20 parts of quartz, 30 parts of wollastonite and 10 parts of calcined zinc oxide; the particle size of fluxing block II is 130 μm, and the thermal expansion coefficient of fluxing block II is 2.5×10 -6 / ℃, calculated by mass percentage, the chemical composition of flux block II includes SiO 2 60%、Al 2 O 314%, Fe 2 O 3 0.50%, TiO 2 0.05%, CaO 8%, MgO 0.30%, K 2 O 5%, Na 2 O 1.0%, ZrO 2 0.30%, ZnO 0.60%, B 2 0 3 8% and Ba0 0.50%, the rest is loss on ignition;

[0117] E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, raise the temperature from room temperature to 1175-1185°C at a heating rate of 12°C / min and keep it warm for 24 hours, then cool it down to room temperature at a cooling rate of 12°C / min to complete the repair.

[0118] Comparative group

[0119] Comparative Example 1

[0120] The repair process and raw materials of Comparative Example 1 are the same as those of Example 1, except that glass fiber is not added to the repair base material formula in Comparative Example 1.

[0121] Comparative Example 2

[0122] The repair process and raw materials of Comparative Example 2 are the same as those of Example 1, except that no kyanite powder is added to the repair base material formula in Comparative Example 2.

[0123] Comparative Example 3

[0124] The repair process and raw materials of Comparative Example 3 are the same as those of Example 1, except that the flux blocks I and II in the repair base material formula of Comparative Example 3 are both flux blocks with a ratio of potassium oxide to sodium oxide of 1:1.

[0125] The defects of the ceramic glaze were repaired by using different repairing processes in the above embodiments and comparative examples, and the repairing effects of the defects of the ceramic glaze obtained by using different repairing processes in the above embodiments and comparative examples were observed. The thermal shock resistance and firing shrinkage rate of the repair layer of the ceramic glaze were tested, and the test results are shown in Table 1 below.

[0126] Table 1 Performance test results of the repair layer obtained by different repair processes

[0127]

[0128] A repairing process for ceramic glaze defects has a repairing layer with low shrinkage and is not prone to cracking. It not only increases the range of repairable defects, but also makes the repaired ceramic glaze defect smooth and flat, and has no color difference from other parts of the ceramic glaze, ensuring aesthetics.

[0129] In Comparative Example 1, since no glass fiber is added, the strength and firing shrinkage of the repair base material are increased, and the strength and firing shrinkage after repair are increased, which leads to uneven glaze surface after repair, cracks, and poor thermal shock resistance.

[0130] In Comparative Example 2, since no kyanite powder was added, the volume shrinkage of the flux component in the repair base material after high-temperature calcination could not be completely offset, resulting in a very large firing shrinkage rate. The repaired glaze surface was uneven and cracked, and had poor thermal shock resistance.

[0131] In Comparative Example 3, since flux block I and flux block II are flux blocks with a potassium oxide to sodium oxide ratio of 1:1, the strength and firing shrinkage rate after repair are increased. The strength and firing shrinkage rate after repair are increased, and the repaired glaze surface is uneven and cracked, and the thermal shock resistance is poor.

[0132] It should be noted that the repair layer refers to a repair layer composed of a repair base layer and a repair surface layer.

[0133] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A process for repairing ceramic glaze defects, characterized in that: The following steps are involved: A. Grinding the defects of the ceramic into a U-shaped groove, and wetting the U-shaped groove to obtain the pretreated ceramic; B. Filling the repair base material into the U-shaped groove of the pretreated ceramic and compacting it to obtain a repair base layer; wherein, calculated by weight, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of coke gem powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate and 0.2-1 part of glass fiber, and the thermal expansion coefficient of the flux block I is (2-3)×10 -6 / ℃; C. drying and grinding the repair bottom layer in sequence to make the surface of the repair bottom layer flush with the surface of the pretreated ceramic; D. filling the repair glaze on the surface of the repair base layer and compacting it to form a repair surface layer; E. Place the pretreated ceramic with the repaired surface layer in a shuttle kiln, heat the shuttle kiln from room temperature to 1175-1185°C at a heating rate of 10-15°C / min and keep it warm for 23-25h, then cool it down to room temperature at a cooling rate of 10-15°C / min to complete the repair.

2. A ceramic glaze defect repair process according to claim 1, characterized in that: In step B, the repair base material further comprises sodium carboxymethyl cellulose solution, glycerol and a preservative; Calculated by mass, the repair base material includes 30-40 parts of waste porcelain powder, 15-25 parts of pyrope powder, 25-35 parts of kyanite powder, 5-15 parts of flux block I, 2-10 parts of zirconium silicate, 0.2-1 part of glass fiber, 2-6 parts of sodium carboxymethyl cellulose solution, 0.2-1 part of propylene glycol and 0.2-1 part of preservative.

3. A ceramic glaze defect repair process according to claim 2, characterized in that: In step D, the repair glaze includes 85-95 parts of glaze slurry I, 10-15 parts of glaze slurry II, 2-10 parts of flux block II and 0.2-0.5 parts of glycerol, calculated by weight. Calculated by weight, the glaze slurry I includes 15-25 parts of feldspar, 20-30 parts of quartz, 3-5 parts of dolomite, 8-15 parts of wollastonite, 5-10 parts of calcium carbonate, 4-6 parts of kaolin, 3-5 parts of calcined alumina, 1-3 parts of calcined zinc oxide and 8-10 parts of zirconium silicate; Calculated by weight, the surface glaze slurry II includes 40-50 parts of feldspar, 15-25 parts of quartz, 20-30 parts of wollastonite and 10-20 parts of calcined zinc oxide.

4. A ceramic glaze defect repairing process according to claim 3, characterized in that: The particle sizes of the flux block I and the flux block II are both ≤160 μm; Calculated by mass percentage, the chemical compositions of the flux block I and the flux block II include SiO2 60-68%, Al2O3 6-14%, Fe2O3 0.10-0.50%, TiO2 0.01-0.05%, CaO 4-12%, MgO 0.15-0.5%, K2O 2-5%, Na2O 0.5-1.5%, ZrO2 0.10-0.50%, ZnO 0.20-0.60%, B2O3 8-12% and Ba00.30-0.60%, and the rest is loss on ignition.

5. A ceramic glaze defect repairing process according to claim 1, characterized in that: The diameter of the glass fiber is ≤30 mm.

6. A ceramic glaze defect repairing process according to claim 1, characterized in that: In step B, the thickness of the repair bottom layer is 8 to 10 μm; In step D, the thickness of the repair surface layer is 3 to 5 μm.

7. A ceramic glaze defect repairing process according to claim 1, characterized in that: The particle size of the coke gemstone powder is ≤200 μm; According to the mass percentage, the particle size of the kyanite powder is: after passing through a 200-mesh sieve, the residue is 60-70%; According to mass percentage, the particle size of the zirconium silicate is: passing through a 325-mesh sieve, the residue is 0-0.5%.

8. The ceramic glaze defect repairing process according to claim 1, characterized in that: The particle size of the waste porcelain powder is ≤200 μm; Calculated by mass percentage, the chemical composition of the waste porcelain powder includes SiO2 65-73%, Al2O3 19-27%, Fe2O3 1-2%, TiO2 0.01-0.1%, CaO 0.5-1.5%, MgO 0.01-0.05%, K2O 2.5-3.5% and Na2O 0.5-1%, and the rest is loss on ignition.

9. A ceramic glaze defect repairing process according to claim 1, characterized in that: The specific steps in step A are: firstly, a carbon rod vibration pen is used to grind the defective part of the ceramic into a U-shaped groove, and after the ground ceramic powder is blown away with an air gun, a wet towel is used to wipe and wet the U-shaped groove to obtain a pretreated ceramic.

10. A ceramic glaze defect repairing process according to claim 3, characterized in that: In step B, the preparation method of the repair base material is: after mixing the formula amount of waste porcelain powder, coke sapphire powder, kyanite powder, flux block I and zirconium silicate evenly, an intermediate slurry I is obtained; then the formula amount of glass fiber, sodium carboxymethyl cellulose, glycerol and preservative are added to the intermediate slurry I, and the repair base material is obtained after stirring evenly; In step D, the preparation method of the repair glaze is: after evenly mixing the formulated amount of glaze slurry I, glaze slurry II and flux block II, an intermediate slurry II is obtained; and after evenly mixing the formulated amount of propylene glycol into the intermediate slurry II, a repair glaze is obtained.

Citation Information

Patent Citations

  • Repairing method for sanitary ware

    CN103102174A

  • Repair material and repair method for sanitary ceramics

    CN103771902A

  • Ceramic patching primer, patching overglaze, preparation methods and ceramic patching method

    CN110590406A

  • Golden yellow pigment for ceramic ink jet printing and preparation method thereof

    CN110804344A

  • Repairing material and repairing method thereof applied to high piezoelectric ceramic bodies

    CN110922215A

Cited By

  • Method for repairing green body

    CN120398573A

  • Repair process for ceramic glaze defects

    CN120620399A